River monitoring of mercury using a novel molybdenum-reducing enzyme assay - Othman, Ahmad Razi; Ahmad, Siti Aqlima; Baskaran, Gunasekaran; Halmi, Mohd Izuan Effendi; Shamaan, Nor Aripin; Syed, Mohd. Arif; Abd. Shukor, Mohd. Yunus (Hibiscus Publisher, 2014)
An inhibitive assay for mercury using a molybdenum-reducing enzyme assay system from Serratia sp. Strain DRY8 is presented. Mercury showed a sigmoidal inhibition curve with a calculated IC50 using the four-parameter logistic model of 2.101 mg l-1. The limit of detection (LOD) and limit of quantitation (LOQ) for mercury were 0.021 and 0.237 mg l-1, respectively. Other heavy metals tested at the final concentrations of 5.0 mg l-1 were not inhibitory to the assay. The enzyme requires 12-molybdophosphoric acid as an electron acceptor substrate and NADH as the electron donor substrate. The enzyme in the crude extract converted the yellowish solution into a deep blue solution with a maximum peak at 865 nm and a shoulder at 710 nm. The comparative IC50 (concentration causing 50% inhibition) data for lead for different toxicity tests show that the IC50 value for mercury was lower than the synthetic activated sludge assay and within the range of the Spirillum volutans and the dehydrogenase activity assays. A water sample from the Juru Industrial estate gave positive toxicity results with mercury far exceeding the maximum permissible concentrations allowed by the Malaysian Department of Environment. The waters from tap, a forest reserve, and a recreational area gave negative toxicity for mercury in agreement with ICP-AES results which showed the presence of heavy metals at the non-detectable levels.